Gambaran Kepadatan Tungau Debu Rumah Spesies Dermatophagoides pteronyssinus dan Dermatophagoides farinae di Kelurahan Jati Kecamatan Padang Timur Kota Padang - Febby Arrahmi; Nuzulia Irawati; Rauza Sukma Rita (Dampak, 2019)
House dust mite is closely associated with the incidence of allergies such as asthma, atopic dermatitis and allergic rhinitis. Spesies of house dust mite which has been proven to be related with the incidence of allergies are Dermatophagoides pteronyssinus and Dermatophagoides farinae. The purpose of this study is to describe the density of house dust mites speciesÂ  in residence houses in Kelurahan Jati. The study was a descriptive study with 96 samples taken fromÂ  two habitats, namely beds and carpets in 48 homes that have been selected randomly. House dust mites were identified using a light microscope with magnification of 40 times. The results showed that 56 of 96 samples were positive of house dust mites. This study showed that Dermatophagoides pteronyssinus was the most commonly found spesies of house dust mite (71 mites) with the highest density in the bed (6.88 mites/ gram of dust). Species Dermatophagoides farinae only found as many as 5 mites with the highest density in the carpet (0.46 mites/ gram of dust). The conclusion of this research is the density of house dust mites in Kelurahan Jati are quite low so that the possibility to cause allergic diseases is very small.